Labour at risk - Vasco Botelho; Claudia Foroni; Andrea Renzetti (European Central Bank (ECB), 2023)
We propose a Bayesian VAR model with stochastic volatility and time varying skewness to estimate the degree of labour at risk in the euro area and in the United States. We model the asymmetry of the shocks to changes in the unemployment rate as a function of real activity and financial risk factors. We find that the conditional distribution of the changes in the unemployment rate displays time-varying volatility and skewness, with peaks coinciding with the Global Financial Crisis and the COVID-19 pandemic. We take advantage of the multivariate nature of our parametric model to measure stagflation risk defined as the possible joint event of large increases in the unemployment rate and large annual rates of inflation. We find an increasing risk of stagflation for the euro area in 2022 while in the United States stagflation risk increased earlier in 2021 and started decreasing more recently. Notwithstanding the significantly high levels of inflation, stagflation risks have been contained by the resilient performance of the labour market in both areas. The degree of labour at risk is therefore important for the assessment of the inflation-unemployment trade-off.
Keywords: C32; C53; E24; E27; 330; Unemployment risk; Stagflation risk; Labour Market; Bayesian Econometrics